2021
DOI: 10.1002/chem.202100975
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Total Synthesis of the Putative Biosynthetic Intermediate Ambruticin J

Abstract: The family of anti-fungal natural products known as the ambruticins are structurally distinguished by a pair of pyran rings adorning a divinylcyclopropane core. Previous characterization of their biosynthesis, including the expression of a genetically modified producing organism, revealed that the polyketide synthase pathway proceeds via a diol intermediate, known as ambruticin J. Herein, we report the first enantioselective total synthesis of the putative PKS product, ambruticin J, according to a triply conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 57 publications
(129 reference statements)
0
5
0
Order By: Relevance
“…The influence of ambruticin VS3 on soil myxobacteria has recently been studied, and results showed that they are beneficial for the environment by preventing the emergence of antagonistic myxobacterial species. In 2021, Trentadue et al [53] reported the total synthesis of ambruticin J by utilizing the Corey-Seebach reagent as a key step. For this purpose, dithiane 34 (synthesized from propargyl alcohol) was reacted with epoxide 35 by using the Corey-Seebach reaction to afford compound 36 with a 70% yield, and after a few steps, vinyl iodide 37 was formed.…”
Section: Ambruticin J Synthesismentioning
confidence: 99%
“…The influence of ambruticin VS3 on soil myxobacteria has recently been studied, and results showed that they are beneficial for the environment by preventing the emergence of antagonistic myxobacterial species. In 2021, Trentadue et al [53] reported the total synthesis of ambruticin J by utilizing the Corey-Seebach reagent as a key step. For this purpose, dithiane 34 (synthesized from propargyl alcohol) was reacted with epoxide 35 by using the Corey-Seebach reaction to afford compound 36 with a 70% yield, and after a few steps, vinyl iodide 37 was formed.…”
Section: Ambruticin J Synthesismentioning
confidence: 99%
“…Taylor et alsynthesised Ambruticin J 379 for the first time utilizing Julia-Kocienski olefination . [100] The Pd-catalysed Suzuki coupling of 375 a with vinyl iodide 374 a in the presence of Tl 2 CO 3 as base afforded 86% yield of E,E-diene, which then underwent oxidation of the alcohol group, providing 376 a with 93% yield. In this study, Julia-Kocienski olefination was carried out between 376 a and sulphone 377 a in the presence of KHMDS in DME as solvent, and gave 51 % yield of the Ealkene 378 a. Ambruticin J 379 was obtained from this Eolefinic compound after a series of chemical transformations (Scheme 74).…”
Section: Chemistryselectmentioning
confidence: 99%
“…14 Total syntheses of just two members of this family of natural products, ambruticin S and ambruticin J, have been described. 15–21…”
Section: Introductionmentioning
confidence: 99%
“…14 Total syntheses of just two members of this family of natural products, ambruticin S and ambruticin J, have been described. [15][16][17][18][19][20][21] In 2006, Reeves reported analysis of the ambruticin biosynthetic gene cluster (BGC) and proposed several unusual features of the modular biosynthetic pathway based on the results from isotopic labelling studies alongside gene knockout experiments. 22 In the tailoring phase of the polyketide pathway, the THP ring is proposed to be formed by the AmbJ catalysed 6,7epoxidation of ambruticin J (1), followed by selective intramolecular attack on the oxirane ring to afford ambruticin F (2) (Scheme 1A).…”
Section: Introductionmentioning
confidence: 99%